Development of Circular Motion Simulation Assisted by Microsoft Excel Spreadsheets to Create Fun Physics Learning - I Gede Purwana Edi Saputra (Jurnal Pendidikan Fisika Undiksha, 2025)
Many physics topics are abstract in nature adds to the difficulty of students understanding them. Such abstract concepts are difficult for students to understand and are difficult for them to establish a complete comprehension of due to their inherent complexity and lack of intuitiveness. One of that concept is Circular Motion. The purpose of this research is to develop the simulation model of Circular Motion using Microsoft Excel Spreadsheets. The method used was Research dan Development (R&D) through modification on steps of 4D Models into 3D Models (Define, Design, and Develop). The result show that through the phases of define, design, and develop, a simulation of circular motion has been successfully created, and utilizing a spreadsheet excel for simulation making teachers can integrate the circular motion simulation technique in their classrooms through various strategie. It can be concluded that Simulating circular motion using Excel spreadsheets provides an accessible and versatile method of teaching and learning this fundamental physics concept for fun physics learning.